A Comparative Analysis of the Efficacy of Mulligan Bent Leg Raising Versus Slump Stretching Combined with SWD in Mechanical Low Back Pain - Okkagani Berranghi Obuun (AKADEMI SERTIFIKASI PROFESI INTERNASIONAL, 2025)
The problem statement: Low back pain (LBP) is the most prevalent, self-reported form of musculoskeletal pain, frequently recurrent, and carries significant socio-economic implications. Approximately eighty percent of low back pain is attributed to